Demographic Characteristics of Patients with COVID in Private Tertiary Hospital in Islamabad - Sajjad Naseer, Qasim Nawaz, Aima Hameed, Imran Khan, Wajiha Gul, Asad Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: the demographic characteristics of 100 COVID-19 patients from a private tertiary hospital in Islamabad were examined. The majority of the patients (72% of whom were female) were married (62%) and from the lower middle class (76%), with a median age of between 30 and 50 (47%). 57% of the patients were employed, putting them in a middle-class socioeconomic situation. The most often reported underlying comorbidities were coronary artery disease (5%), chronic lung disease (13%), diabetes (42%), and hypertension (47%). These results highlight the need to increase public awareness of the warning signals and preventative actions for this condition in vulnerable populations. Objective: In this study, the socioeconomic level, age, and gender of patients with COVID-19 who were being treated at a private tertiary hospital in Islamabad, Pakistan, were examined. Methods: The demographic information of 100 patients hospitalized with COVID-19 at a private tertiary hospital in Islamabad between January 2021 and January 2022 was examined in a retrospective research that we carried out. From patient records and medical reports, we gathered information on the patient's age, gender, socioeconomic position, present and underlying comorbidities, and other pertinent features. Results: The bulk of the patients (72% of whom were female) were aged between 30 and 50 (47%), were married (62%) and were from the lower middle class (76%). In terms of socioeconomic position, 57% of the patients were employed. Hypertension (47%), diabetes (42%), chronic lung disease (13%), and coronary artery disease (5%) were the most frequently reported underlying comorbidities. Conclusion: The findings highlight the need to raise public knowledge of the danger signs and protective measures for this illness in susceptible groups. Further study is required to understand the root causes of COVID-19 in Pakistan fully. Keywords: COVID-19, demographic characteristics, Islamabad, private tertiary hospital